Distribution and characteristic of deposit-feeder crabs (Crustacea: Brachyura) in some mangrove ecosystem types in Lombok Island - Dewi Citra Murniati (The East Java Biological Society, 2015)
Lombok Island consists of five different mangrove forest types with various pattern of fauna distribution. These pattern variations were constructed by different type of substrates. Deposit feeder crabs play an important role in determination of substrate pattern. The objective of this study was to investigate the distribution pattern of some crabs which their characteristics are correlated to the mangroves substrate. Crabs were collected from eight locations in Mangrove area of Lombok Island. Ten species of the deposit feeder crab were identified, their distribution pattern was illustrated based on the result of field observation on their morphological characteristics. The highest species diversity found in Teluk Rasu and Tanjung Luar. Both cheliped and maxilliped characteristics represent to habitat preference. Uca annulipes, U. perplexa, U. vocans, and Dotilla myctiroides inhabited sandy substrate, while U. bellator, U. demani, U. dussumieri, U. forcipata, U. triangularis, and Tmethypocoelis ceratophora inhabit muddy substrate.